2020
DOI: 10.20944/preprints202007.0334.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role of Alpha-Synuclein And Other Parkinson’s Genes in Neurodevelopmental and Neurodegenerative Disorders

Abstract: Neurodevelopmental and late-onset neurodegenerative disorders present as separate entities that are clinically and neuropathologically quite distinct. However, recent evidence has highlighted surprising commonalities and converging features at the clinical, genomic, and molecular level between these two disease spectra. This is particularly striking in the context of autism spectrum disorder (ASD) and Parkinson’s disease (PD). Genetic causes and risk factors play a central role in disease pathophysio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 257 publications
(337 reference statements)
0
4
0
Order By: Relevance
“…Notably, the variation that was identified in TRIM41 affects its PRY-SPRY domain [ 131 ]. In addition, SNCA gene deletions and partial duplication have been found in ASD patients [ 135 , 136 ]. As accumulating arguments suggest that α-synuclein may be involved in ASD pathogenesis [ 136 ], it is tempting to speculate that TRIM17 may also play a role in ASD by altering α-synuclein expression through its action on TRIM41 and ZSCAN21.…”
Section: Trim17 and Diseasesmentioning
confidence: 99%
“…Notably, the variation that was identified in TRIM41 affects its PRY-SPRY domain [ 131 ]. In addition, SNCA gene deletions and partial duplication have been found in ASD patients [ 135 , 136 ]. As accumulating arguments suggest that α-synuclein may be involved in ASD pathogenesis [ 136 ], it is tempting to speculate that TRIM17 may also play a role in ASD by altering α-synuclein expression through its action on TRIM41 and ZSCAN21.…”
Section: Trim17 and Diseasesmentioning
confidence: 99%
“…A recent study reported a strong association between neurodegenerative and neurodevelopmental disorders, specifically PD and ASD [11]. This association includes genetic, molecular, and even clinical similarities between these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Other symptoms include early dystonia, history of seizures, and neuropsychiatric symptoms [5] . 22q11DS-associated PD has clinical and neuropathological features similar to sporadic PD and some cases of hereditary PD [6] .…”
mentioning
confidence: 98%
“…It has recently been recognized that adults with 22q11DS are at an increased risk of developing Parkinson disease (PD) [5] . Clinically, the onset of symptoms is asymmetric and is typically accompanied by progressive bradykinesia, rigidity, and tremor [6] . Typically, patients respond well to levodopa therapy [7] .…”
mentioning
confidence: 99%